4(2x-7)=2x+3(4x+1)

Simple and best practice solution for 4(2x-7)=2x+3(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-7)=2x+3(4x+1) equation:



4(2x-7)=2x+3(4x+1)
We move all terms to the left:
4(2x-7)-(2x+3(4x+1))=0
We multiply parentheses
8x-(2x+3(4x+1))-28=0
We calculate terms in parentheses: -(2x+3(4x+1)), so:
2x+3(4x+1)
We multiply parentheses
2x+12x+3
We add all the numbers together, and all the variables
14x+3
Back to the equation:
-(14x+3)
We get rid of parentheses
8x-14x-3-28=0
We add all the numbers together, and all the variables
-6x-31=0
We move all terms containing x to the left, all other terms to the right
-6x=31
x=31/-6
x=-5+1/6

See similar equations:

| 2x+8/2+5=x+9 | | y-4=y=6 | | 12x12=144 | | 0.75x+4=1.25x | | 4^-x+3=97 | | 6x-6(-8x-17)=-6 | | 7x+4=47 | | -1+6x+4x+5=x | | 4x+5-1+6x=x | | 3x-4+5x=-18 | | 14x-6=-20 | | G=(x×x)-3x+1 | | 7r+4-4r=10+9r | | 256^x+2=8^2x-3 | | 2x^2-42x+12=0 | | 0.8(x-15)=-0.8x-12 | | (b3)4=9 | | 1x+56+1x+91=180 | | 2(x-8)^2=50 | | 2x+42=3x-27 | | -2y+12y=18 | | 2x+54=82 | | 2x+5*1/10=1 | | (x^2)+2x+2=(x^2)-3+10x-30+x+6 | | 3j-2=2j+6 | | -2.2+u/3=-9.7 | | 6y+4-2=28 | | 2*1/4+5y=1 | | 28=x*x | | 3n+6n=16 | | 60x+40*1/10=19 | | A(b)=58+b |

Equations solver categories